(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Weed management in a sustainable way is the ultimate target of Agronomists to maximize crop yield per unit area. To develop a sustainable weed management technique, an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to study the effect of different weed management techniques on the performance of wheat cultivars. The experiment comprised three wheat cultivars; viz. BARI Gom-28, BARI Gom-29 and BARI Gom-30 and five weed management techniques namely, no weeding (W0), two hand weedings (HW) at 20 DAS and 40 DAS (W1), use of rice straw mulch @ 6 t ha–1 (W2), use of pre emergence herbicide Panida @ 1 L ha–1 (W3) and use of pre emergence herbicide + one hand weeding (HW) at 40 DAS (W4). The experiment was laid out in a split-plot design with three replications. The experimental plots were infested by different weed species. Annual weeds were outnumbered than perennial and constitute 84.74% against 15.26%, respectively. Among them, the five most dominant weed species based on the importance value in descending order were Polygonum orientale>Chenopodium album >Cynodon dactylon>Sonchus arvensis>Cyperus rotundus and rest of the weed species represent 8.94%. Wheat cultivar BARI Gom-29 produced the highest grain yield (3.44 t ha–1). The highest grain yield (3.29 t ha-1) was obtained from the application of pre emergence herbicide Panida @ 1 L ha–1. But in case of interaction BARI Gom-29 in combination with use of rice straw mulch @ 6 t ha-1 produced the highest grain yield (4.36 t ha–1). The highest grain yield obtained due to highest number of total and effective tillers hill-1 and highest number of grains spike-1 in BARI Gom-29 with application of rice straw mulch @ 6 t ha–1. From the results of the study it may be concluded that BARI Gom-29 with application of rice straw mulch @ 6 t ha–1 technique appears to be the promising technology in controlling weeds as well as obtaining higher grain yield of wheat. J. Bangladesh Agril. Univ. 16(3): 437–443, December 2018